2017
DOI: 10.1089/neu.2015.4364
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines and Paroxysmal Sympathetic Hyperactivity after Traumatic Brain Injury

Abstract: Paroxysmal sympathetic hyperactivity (PSH) affects a significant minority of people in the intensive care unit after severe traumatic brain injury. Systematic research has yet to elucidate or quantify the extent of the role of the catecholamines or adrenocortical and thyroid axis hormonal influences in the condition. Data were prospectively collected on 80 consecutive patients, 18 of whom developed clinical signs of PSH (22.5%). Catecholamine and hormonal data were collected sequentially at 4-h intervals or du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 42 publications
(60 reference statements)
0
27
0
4
Order By: Relevance
“…In the neurotransmitter system, paroxysm derives from uncontrollable adrenergic outflow resulting in increased circulating catecholamine (34,35). Research suggests that levels of adrenocorticotropic hormone (ACTH), epinephrine (E), norepinephrine (NE), and dopamine (D) significantly increase during paroxysm, while NE and D decrease, rather than ACTH and E, during the intermittent period (4,17,36). This is because NE and D arise from increased excitability of the sympathetic nervous system, whereas E is almost exclusively derived from the adrenal medulla (37).…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…In the neurotransmitter system, paroxysm derives from uncontrollable adrenergic outflow resulting in increased circulating catecholamine (34,35). Research suggests that levels of adrenocorticotropic hormone (ACTH), epinephrine (E), norepinephrine (NE), and dopamine (D) significantly increase during paroxysm, while NE and D decrease, rather than ACTH and E, during the intermittent period (4,17,36). This is because NE and D arise from increased excitability of the sympathetic nervous system, whereas E is almost exclusively derived from the adrenal medulla (37).…”
Section: Pathophysiologymentioning
confidence: 99%
“…This is because NE and D arise from increased excitability of the sympathetic nervous system, whereas E is almost exclusively derived from the adrenal medulla (37). In general, there is about a 2-or 3-fold increase in catecholamine and an ∼40% increase in adrenocortical hormones in serum (17,38). Changes in the neurotransmitter system, driven by stimuli, highlight the importance of considering the triggering event in pathogenetic research.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the initial report (Baguley et al 2014), non-specific nature of PSH-AM in the differential diagnoses may be a limitation of this diagnostic tool in the ICU settings; the present patients 2 and 6 required a few weeks to be diagnosed as PSH after onset of the PSH features due to the concomitant diseases that mimicked PSH. Although early diagnostic biomarkers of PSH have yet to be developed, a very recent study has shown that plasma catecholamine concentrations markedly increased during PSH episodes (Fernandez-Ortega et al 2017), indicating additional usefulness of catecholamine levels for early diagnosis of this disorder. More recently, an observational cohort study of traumatic brain injury patients with impaired consciousness (GCS score ≤ 12) has shown that early fever might be an indication of autonomic dysfunction; among the clinical feature scale items of PSH-AM (Table 1), higher temperature scores within 3 days after ICU admission were associated with the development of PSH, indicating that early fever may be a herald of PSH following severe traumatic brain injury (Hinson et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2,7,23 Each episode has a rapid and often sudden onset. Most episodes are triggered by external stimulation, 24 but some may occur without an apparent trigger. Several signs of sympathetic excess must occur simultaneously to support the diagnosis of PSH, but not all manifestations of sympathetic hyperactivity need to be present with each episode.…”
Section: Diagnosismentioning
confidence: 99%